Commentary: The legal system response to child maltreatment - Cross, Theodore P. (Child maltreatment, 2023)
Legal actions are perhaps the most powerful responses to child maltreatment. Criminal and child protection investigation and forensic interviewing can provide the evidence needed to support a child victim’s disclosure. Prosecution of child maltreatment can hold perpetrators accountable. Juvenile and family court actions can provide for children’s safety and oversee their care in state custody and journey to a permanent home. This commentary introduces readers to a special issue of the journal Child Maltreatment that focuses on the legal system response to child abuse and neglect. We provide an overview of the issue’s 11 research articles and additional commentary. These works provide crucial new knowledge on gaining information from child victims involved in the legal system, on the law enforcement and prosecution response to child maltreatment, and on the legal framework supporting child protection.